Early decompression following cervical spinal cord injury: examining the process of care from accident scene to surgery - Battistuzzo, C.; Armstrong, A.; Clark, J.; Worley, L.; Sharwood, L.; Lin, P.; Rooke, G.; Skeers, P.; Nolan, S.; Geragthy, T.; Nunn, A.; Brown, D.; et al. (2015)
Early decompression may improve neurological outcome after spinal cord injury (SCI), but is often difficult to achieve because of logistical issues. The aims of this study were to determine (1) the time to decompression in cases of isolated cervical SCI in Australia and New Zealand and (2) where substantial delays occur as patients move from the accident scene to surgery. Data were extracted from medical records of patients aged 15-70 years with C3-T1 traumatic SCI between 2010 and 2013. A total of 192 patients were included. The median time from accident scene to decompression was 21h, with the fastest times associated with closed reduction (6h). A significant decrease in the time to decompression occurred from 2010 (31h) to 2013 (19h, p = 0.008). Patients undergoing direct surgical hospital admission had a significantly lower time to decompression compared to patients undergoing pre-surgical hospital admission (12h vs. 26h, p < 0.0001)). Medical stabilisation and radiological investigation appeared not to influence the timing of surgery. The time taken to organise theatre following surgical hospital admission was a further factor delaying decompression (12.5h). There was a relationship between the timing of decompression and the proportion of patients demonstrating substantial recovery (2-3 AIS grades). In conclusion, the time of cervical spine decompression markedly improved over the study period. Neurological recovery appeared to be promoted by rapid decompression. Direct surgical hospital admission, rapid organisation of theatre and where possible use of closed reduction, are likely to be effective strategies to reduce the time to decompression.